Penerapan Pengendali Suhu pada Proses Pasteurisasi Susu dengan Menggunakan Metode PID Ziegler-Nichols - Setyawan, Hendra Putra; Fahruzi, Akhmad (Institut Teknologi Adhi Tama Surabaya, 2024)
The milk pasteurization process is an effective method to eliminate pathogenic bacteria and extend the shelf life of milk. Based on the SNI 19-1502-1989 standard, pasteurized milk occurs at a temperature between 63 and 66 °C for at least 30 minutes (low temperature long time) or at 72 °C for at least 15 seconds (high temperature short time). Previous research has only studied one process, either HTST or LTLT, and compared the fuzzy, PI, and PID methods. This research shows the superiority of the PID method, which has been refined by previous studies and adopted as a method for the milk pasteurization process. It applied the PID method to two processes, HTST and LTLT, for milk pasteurization. The test results indicated that this system required only about ±1 hour and 7 minutes for both PID processes, compared to traditional methods. In addition, this system showed a performance comparison between the Ziegler-Nichols PID and Trial-Error methods in terms of rise time, delay time, overshoot, and steady-state error.